Psychometric Properties of an Agriculture Teacher Efficacy Scale for Senior Secondary Schools in Eswatini - Mathenjwa, Mpendulo; Dlamini, Marietta P. (Advances in Social Sciences Research Journal, 2019)
Teacher efficacy is an important motivational attribute influencing teacher performance and student learning outcomes. Teacher efficacy is multidimensional yet inconsistencies exist on the nature of construct that best measure teacher efficacy across different subjects and contexts. The purpose of the study was to explore the psychometric properties of the agriculture teacher efficacy scale adapted from the Teacher Self-Efficacy Scale (TSES) of Tschannen-Moran and Hoy (2001). Data were collected from 161 beginning agriculture teachers at senior secondary schools in Eswatini. Item analysis and exploratory factor analysis (EFA) using principal component and verimax rotation were used to analyse the data. The findings indicate that the agriculture teacher efficacy scale was reliable (.92) with inter-item correlation value of .41 to .67 and items discrimination index of ≥ .40). EFA revealed that the agriculture teacher efficacy scale had four factors explaining 47.7% of variance among the items which were instructional strategies, student engagement, classroom management, and practical work management. Conclusion was, the scale is valid to assess agriculture teacher efficacy. Recommendation was, further testing the agriculture teacher efficacy scale across school levels in teaching agriculture.